The role of maintenance in manufacturing sector: An excerpt from review of liturature - Vassu, K.; Mad Lazim, Halim (UUM College of Business, 2016)
The purpose of this study is to reveal the role of maintenance which is integrated to various levels of the manufacturing sector.Maintenance is a very popular concept in the manufacturing world as well as in some countries in the developing world.The study explores the degree of maintenance implementation in manufacturing plants and its impact on manufacturing organization.This study was designed based on the maintenance approach from various authors, to provide detailed explanation to readers on the role of maintenance practices in reducing manufacturing costs and in providing more economical, quality services compared to the in‐house workforce.